Service Quality And Its Relationship With Customer Satisfaction Towards Customer Loyalty - MOHD ISA, SALMI (2005)
This research was conducted to find and get a better understanding of service quality level and to examine the relationship between service quality, customer satisfaction and customer loyalty with the services offered by the audit firms. SERVQUAL model will be used to measure the public listed companies perception and expectation with the audit services received.